Electret electrostatic treatment film and preparation process thereof
The electret electrostatic therapy membrane prepared by composite nanofiber materials and charge injection process solves the problems of charge retention and adhesion stability of electret membranes, and achieves stable electric field output and long-term use effect in complex environments.
Patent Information
- Application Number
- CN202511221461.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-16
AI Technical Summary
Existing electret films have shortcomings in charge retention, adhesion stability, and durability over multiple cycles. In particular, they are prone to charge dissipation, structural fatigue, and detachment in complex environments, failing to meet the technical requirements for long service life and repeated use.
A composite nanofiber material consisting of fluorinated polyether ester, nano-cerium oxide particles, graphene quantum dots, carboxymethyl chitosan, and sodium hyaluronate was used to prepare an electret electrostatic therapeutic membrane through electrospinning and charge injection processes. The membrane was then bonded to a flexible silicone gel adhesion layer and covered with a release film to maintain structural integrity.
It improves the charge retention capacity, adhesion stability and multi-cycle durability of the membrane, ensuring stable electric field output and interface adhesion performance even in high temperature or high humidity environments, making it suitable for long-term and repeated use in medical or therapeutic scenarios.
Smart Images

Figure BDA0005571518280000211
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to an electret electrostatic therapeutic membrane and its preparation process. Background Technology
[0002] Currently, in the fields of electrostatic therapy, skin stimulation modulation, and dielectric-assisted medicine, functional membrane materials with electret properties are increasingly being used to achieve non-invasive electric field effects and continuous physiological response regulation. Traditional electret membranes are mostly based on polymer films, achieving basic charge storage through a monolayer structure. However, in actual clinical or adhesive applications, these membranes often suffer from poor charge retention, limited lifespan, and insufficient adhesion stability, making it difficult to meet the technical requirements for long-term effectiveness and reusability.
[0003] Especially under complex environmental conditions, such as high humidity, high temperature, or repeated application, the membrane is prone to charge dissipation, structural fatigue, and even detachment, leading to rapid degradation of its electret properties and making it difficult to guarantee therapeutic efficacy. Furthermore, some existing electret membranes fail to achieve synergistic design of electric field and mechanical properties, lack effective stress regulation mechanisms, and cannot cope with structural damage caused by multi-cycle physical disturbances. In addition, the electret process often relies on physical friction or corona discharge, resulting in low charge injection efficiency and poor stability, making it difficult to adapt to functional membrane materials with complex structures.
[0004] Therefore, there is an urgent need to develop a flexible composite membrane structure with excellent electret properties, good adhesion stability and multi-cycle durability, which can maintain stable electric field output and interface adhesion performance in different application environments, thereby breaking through the functional bottleneck of existing technologies and expanding its application boundaries in electrostatic medical and related biomedical fields. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides an electret electrostatic therapeutic membrane and its preparation process, solving the problems of existing electret membranes in terms of charge retention capacity, adhesion stability, and durability over multiple cycles of use.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] The first aspect of this invention provides an electret electrostatic therapeutic membrane, wherein, by weight percentage, the therapeutic membrane comprises a composite nanofiber material with the following components:
[0008] Fluorinated polyether ester 15-20%;
[0009] 1-2% carboxymethyl chitosan;
[0010] The nano-cerium oxide particles comprise 2-5% of the total content, with a particle size of 50-100 nm.
[0011] Graphene quantum dots have a particle size of 0.5-1.0% and a particle size of 5-10 nm.
[0012] Sodium hyaluronate 1-2%;
[0013] The composite components are prepared into a film by electrospinning and then given electret properties through charge injection. Finally, the film is attached to a flexible silicone gel adhesion layer and covered with a peelable protective film to maintain structural integrity before use.
[0014] In this structural design, fluorinated polyether ester serves as the matrix material for the membrane, providing the skeletal support and charge trapping sites for film formation. Its molecular structure contains fluorine, which forms stable polar segments with the polymer backbone, effectively trapping and fixing free electrons during corona discharge to form an electret charge layer. This material selection not only supports the stable formation of the nanofiber structure but also contributes to the formation of a durable surface potential distribution.
[0015] The introduction of nano-cerium oxide particles is one of the key aspects of the material composition in this invention. Cerium oxide, as a rare earth oxide with a reversible valence state, has a Ce... 3+ / Ce 4+ The reversible behavior between these processes provides a redox buffer, enabling the regulation of the charge state of the microenvironment on or inside the membrane surface. During high-voltage electrospinning or corona injection, cerium oxide nanoparticles can temporarily accept or release electrons, thereby promoting the stable injection of electret charges and dynamically regulating charge loss during use, thus enhancing the overall charge maintenance capability of the structure.
[0016] Graphene quantum dots, as a type of carbon nanomaterial, are dispersed in fibrous membrane substrates and play a dual role. On the one hand, their large specific surface area and abundant surface functional groups allow them to form stable physical embeddings or chemical entanglements with the polymer matrix, enhancing the local charge storage capacity of the composite system. On the other hand, their π-conjugated structure provides electron migration pathways, regulating the surface conductivity and local charge density distribution of the membrane. This synergistic effect enables the injected charge to form an adaptive distribution at the microscale, contributing to the formation of a continuous and stable electrostatic field environment.
[0017] Carboxymethyl chitosan, a water-soluble cationic polysaccharide, is distributed within the fiber system. While providing hydrophilicity and biocompatibility, the amino and carboxyl groups in its molecules can interact electrostatically or through hydrogen bonding with the surfaces of cerium oxide or graphene quantum dots, thus forming a physically cross-linked network within the composite structure. This multi-component interaction enhances the structural stability within the fiber and creates slow-release channels for charge migration, resulting in a more uniform distribution of surface potential and reducing the likelihood of localized discharge failure.
[0018] Sodium hyaluronate introduces flexible regulation and bio-friendly characteristics. Its polymer chains have a certain degree of stretchability and local helical structure during the fiber film formation process, which can regulate the morphology and flexibility of nanofibers. This is beneficial for the membrane to adhere closely to irregular curved surfaces such as the skin during application. At the same time, its hydration properties also provide a humidity buffer for the charge layer, reducing the disturbance of charge migration caused by the external environment.
[0019] The five functional components mentioned above work together in the electric field spinning domain to form a composite film with a micron-scale fiber orientation structure. This structure not only ensures overall mechanical flexibility and maneuverability but also provides a multi-level functional synergistic platform for charge trapping, injection, and maintenance. Furthermore, by introducing high-frequency pulsed plasma treatment during the corona injection stage, directional injection of multi-source charges can be achieved on and inside the fiber membrane, further enhancing the electret effect. During plasma treatment, cerium oxide and graphene quantum dots act as charge retention mediators, providing a "trap-transfer-fixation" mechanism in spatial distribution, optimizing the temporal-spatial distribution characteristics of the charge.
[0020] The bonding of the composite membrane to the flexible silicone gel adhesion layer not only ensures good adhesion during application, but also provides long-term environmental isolation for the electret structure due to the electrical insulation and adjustable humidity properties of the silicone gel, reducing the interference of external climate on charge distribution. The release film ensures the membrane is not affected by external electrostatic interference during encapsulation and transportation; after removal, it can be applied to the target area requiring electrostatic treatment.
[0021] Overall, this invention constructs a nano-electrostatic platform with electret stability, flexible structure, and therapeutic interface adaptability through the organic composite and spatial structure design of multifunctional materials. Its mechanism is based on the synergistic charge regulation mechanism between materials and the spatially confined composite structure, which is prominently manifested in the charge slow-release characteristics guided by redox capabilities and the charge transport and stabilization mechanism assisted by carbon nanomaterials.
[0022] Preferably, the flexible adhesive layer is a low-viscosity silicone gel layer with a viscosity of 100-150 mPa·s and a coating thickness of 0.1-0.3 mm.
[0023] Preferably, the fluorinated polyether ester is dissolved in a mixed solvent consisting of tetrahydrofuran and dimethylformamide in a volume ratio of 1:1 to 1.2.
[0024] Preferably, the electret performance is achieved by a pulsed plasma charge injection process, with an injection voltage of 15–20 kV and a corona treatment time of 8–12 minutes.
[0025] A second aspect of the present invention provides a process for preparing the electret electrostatic therapeutic membrane described in the first aspect, comprising the following steps:
[0026] 1) Preparation of fluorinated polyether ester solution: Dissolve fluorinated polyether ester in a mixed solvent composed of tetrahydrofuran and dimethylformamide, and stir at 25-30℃ for 2-3 hours to form a uniform and transparent solution;
[0027] 2) Prepare carboxymethyl chitosan solution and sodium hyaluronate solution respectively, with a concentration of 1-2%, and stir at 25-30℃ for 1-2 hours to obtain a uniform hydrosol;
[0028] 3) Preparation of nano-cerium oxide dispersion and graphene quantum dot dispersion: Nano-cerium oxide particles and graphene quantum dots were added to a mixed solvent of tetrahydrofuran and dimethylformamide, and dispersed by ultrasonic treatment at a power of 100-200W and a time of 30-60min to obtain a uniform dispersion.
[0029] 4) Add the nano-cerium oxide dispersion, graphene quantum dot dispersion, carboxymethyl chitosan solution and sodium hyaluronate solution to the fluorinated polyether ester solution in sequence, and stir for 30-60 minutes to obtain the composite spinning solution;
[0030] 5) Nanofiber membranes were prepared by electrospinning, wherein the spinning voltage was 20-25 kV, the spinning solution spraying rate was 0.6-1.0 mL / h, the distance between the spraying end and the receiving end was 10-12 cm, and the spinning time was 2-3 h.
[0031] 6) The nanofiber membrane is subjected to pulsed plasma charge injection treatment, with the treatment frequency set to 5 kHz, the discharge voltage to 15-20 kV, the treatment time to 8-12 min, the pulse time to 5-7 s, the interval time to 2-3 s, and the treatment environment to air with a relative humidity of 30-35%.
[0032] 7) The treated membrane was left to stand at room temperature for 12–14 hours to stabilize the surface charge;
[0033] 8) The membrane is bonded and assembled with a pre-prepared flexible silicone gel adhesive layer, which is a low-viscosity silicone gel layer with a thickness of 0.1-0.3 mm and a viscosity of 100-150 mPa·s uniformly coated on the surface of the polyethylene terephthalate membrane and dried at 40-45°C for 1-2 hours. After bonding, a release film is applied to obtain the final product.
[0034] Preferably, the ultrasonic dispersion of the nano-cerium oxide dispersion and the graphene quantum dot dispersion uses the same tetrahydrofuran and dimethylformamide mixed solvent as in step 1), the dispersion temperature is room temperature, and the dispersion time is 30-60 min.
[0035] Preferably, the electrospinning process is carried out in an environment with a relative humidity of 30-40% and a temperature of 22-25°C.
[0036] Preferably, the low-viscosity silicone gel layer is obtained by uniformly coating a silicone gel with a thickness of 0.1 to 0.3 mm on the surface of a PET film and drying it at 40 to 45°C for 1 to 2 hours.
[0037] Preferably, the order of addition of the components in the spinning solution is as follows: nano-cerium oxide particles, graphene quantum dots, carboxymethyl chitosan, and sodium hyaluronate.
[0038] Preferably, the final product is vacuum-sealed and stored in an environment with a temperature of 15–25°C, a relative humidity of 30–40%, and protected from light.
[0039] This invention provides an electret electrostatic therapy film and its preparation process. It has the following beneficial effects:
[0040] 1. The composite membrane design of this invention significantly improves the adhesion stability and electrical isolation capability of the membrane to the skin during electrostatic therapy by optimizing the thickness of the silicone gel layer and the electret properties. The appropriate silicone gel thickness not only enhances the flexibility of the membrane and ensures a tight fit between the membrane and the skin surface, but also mitigates electric field disturbances and improves the electrical isolation of the membrane. This design effectively avoids instability phenomena such as edge lifting and detachment of the membrane in practical applications, providing a guarantee for long-term stable treatment effects.
[0041] 2. This invention introduces a charge injection step, enabling the formation of a persistent and stable electret electric field on the membrane surface, thereby enhancing the membrane's electric field activation capability. During electrostatic therapy, charge injection effectively activates the membrane's electrostatic properties, ensuring the continuous maintenance and stable release of charge during treatment, thus ensuring the stable maintenance of the membrane's electret state and improving the continuity and effectiveness of the treatment.
[0042] 3. This invention further enhances the charge retention capability of the membrane under high-temperature environments by introducing heat-stabilizing components. The addition of heat-stabilizing materials effectively improves the stability of the membrane when heated, reduces charge leakage caused by thermal disturbances, and ensures that the membrane maintains stable electrical performance even under environments with large temperature variations. This technological breakthrough provides more applicable scenarios for the wide application of membranes, especially enabling stable operation for longer periods in environments such as high temperatures or applications on the skin.
[0043] 4. The composite membrane design of this invention exhibits excellent multi-cycle stability. During repeated application and peeling processes, the membrane maintains high adhesion and a stable charge distribution, demonstrating its durability in repeated use. The synergistic effect of the flexible support layer and the sustained-release structure ensures that the membrane effectively disperses mechanical stress and maintains its electrical properties. This characteristic makes the membrane suitable for long-term and repeated use in medical or therapeutic scenarios, improving the product's lifespan and performance stability.
[0044] 5. The composite membrane structure of this invention, through precise design and multi-layer synergistic operation, achieves optimized performance of the membrane under different functional requirements. Through the rational combination of materials in each layer, the membrane not only possesses excellent adhesion and electrical isolation but also outstanding charge retention and thermal stability. This design provides new insights for the research and development of electrostatic therapy and medical adhesive materials, possessing strong market competitiveness and application value. Detailed Implementation
[0045] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0046] Example 1:
[0047] This invention provides a process for preparing an electret electrostatic therapeutic film, comprising the following steps:
[0048] S1. Weigh 18wt% of fluorinated polyether ester and dissolve it in a mixed solvent of tetrahydrofuran and dimethylformamide in a volume ratio of 1:1. Stir the solution in a water bath at 28°C for 2.5 hours to obtain a transparent and uniform polymer solution.
[0049] S2. Prepare 1.5 wt% carboxymethyl chitosan aqueous solution and 1.5 wt% sodium hyaluronate aqueous solution respectively, and stir at 28°C for 1.5 hours to obtain a transparent hydrosol.
[0050] S3. Add 3.5 wt% of nano-cerium oxide particles and 0.75 wt% of graphene quantum dots to the same mixed solvent as in step 1, and disperse them by ultrasonic treatment (150 W, 45 minutes) at room temperature to obtain a uniform dispersion.
[0051] S4. Add the nano-cerium oxide dispersion, graphene quantum dot dispersion, carboxymethyl chitosan solution and sodium hyaluronate solution to the fluorinated polyether ester solution in sequence, and stir for 45 minutes to obtain the composite spinning solution.
[0052] S5. Electrospinning was performed at a temperature of 23℃ and a relative humidity of 35%. The spinning voltage was set to 22kV, the jetting rate to 0.8mL / h, the distance between the jetting end and the collecting plate to 11cm, and the spinning time to 2.5 hours, forming a composite nanofiber membrane.
[0053] S6. Processing is performed using a pulsed plasma charge injection device with a frequency of 5kHz, a discharge voltage of 17kV, a processing time of 10 minutes, a pulse / interval time of 6 / 3 seconds, and an ambient humidity of 32%.
[0054] S7. After treatment, the film is left to stand at room temperature for 13 hours to stabilize the surface charge.
[0055] S8. A low-viscosity silicone gel layer with a thickness of 0.2 mm and a viscosity of 125 mPa·s is coated on the surface of the PET film and dried at 43°C for 1.5 hours. The nanofiber membrane after standing is bonded to the silicone gel layer and covered with a release film to obtain the finished electret electrostatic therapy membrane.
[0056] Example 2:
[0057] This invention provides a process for preparing an electret electrostatic therapeutic film, comprising the following steps:
[0058] S1. Prepare a 15wt% fluorinated polyether ester solution by mixing tetrahydrofuran and dimethylformamide in a 1:1 volume ratio, stirring for 2 hours, and setting the temperature to 25℃.
[0059] S2. Prepare 1 wt% aqueous solutions of carboxymethyl chitosan and sodium hyaluronate, respectively, and stir for 1 hour at a temperature of 25°C.
[0060] S3. Add 2wt% nano-cerium oxide particles and 0.5wt% graphene quantum dots to a mixed solvent and ultrasonically disperse for 30 minutes at a power of 100W.
[0061] S4. Add the fluorinated polyether ester solution in the following order: cerium oxide, graphene quantum dots, carboxymethyl chitosan, and sodium hyaluronate. Mix and stir for 30 minutes.
[0062] S5. Spinning conditions are set as follows: temperature 22℃, humidity 30%, voltage 20kV, spray rate 0.6mL / h, nozzle distance from collection plate 10cm, and spinning time 2 hours.
[0063] S6. Charge injection treatment parameters: frequency 5kHz, voltage 15kV, treatment time 8 minutes, pulse / interval time 5 / 2 seconds, humidity 30%.
[0064] S7. Let the membrane stand for 12 hours.
[0065] S8. Coat the surface of the PET film with a silicone gel layer of 0.1 mm thickness and 100 mPa·s viscosity, dry at 40°C for 1 hour, laminate the composite film and cover it to obtain the finished product.
[0066] Example 3:
[0067] This invention provides a process for preparing an electret electrostatic therapeutic film, comprising the following steps:
[0068] S1. Weigh 20wt% of fluorinated polyether ester and dissolve it in a mixed solvent of tetrahydrofuran and dimethylformamide in a volume ratio of 1:1.2. Stir at 30°C for 3 hours.
[0069] S2. Prepare 2wt% aqueous solutions of carboxymethyl chitosan and sodium hyaluronate respectively, and stir at 30°C for 2 hours.
[0070] S3. Add 5wt% nano-cerium oxide particles and 1.0wt% graphene quantum dots to a mixed solvent and sonicate for 60 minutes at a power of 200W.
[0071] S4. Add each solution to the polymer base solution in the predetermined order and stir for 60 minutes to form a composite spinning solution.
[0072] S5. Spinning parameters are set as follows: temperature 25℃, humidity 40%, voltage 25kV, spray rate 1.0mL / h, nozzle distance from collection plate 12cm, and spinning time 3 hours.
[0073] S6. Charge injection processing settings: frequency 5kHz, voltage 20kV, processing time 12 minutes, pulse / interval time 7 / 3 seconds, ambient humidity 35%.
[0074] S7. The membrane is left to stand at room temperature for 14 hours.
[0075] S8. A silicone gel layer with a thickness of 0.3 mm and a viscosity of 150 mPa·s is uniformly coated on the PET film and dried at 45°C for 2 hours to complete the film bonding and release film encapsulation.
[0076] Comparative Example 1:
[0077] The difference from Example 1 is that graphene quantum dots were not added; otherwise, they are the same.
[0078] Comparative Example 2:
[0079] The difference from Example 1 is that the content of the nano-cerium oxide particles used is 6 wt%, while the rest are the same.
[0080] Comparative Example 3:
[0081] Compared with Example 1, the difference is that the coating thickness of the low-viscosity silicone gel adhesion layer is 0.05 mm, while the rest are the same.
[0082] Comparative Example 4:
[0083] The difference from Example 1 is that pulsed plasma charge injection was not performed; all other aspects are the same.
[0084] Comparative Example 5:
[0085] Compared to Example 1, the difference is that the fluorinated polyether ester was dissolved using a single dimethylformamide (DMF) solvent instead of a THF / DMF mixed solvent system; otherwise, they are the same.
[0086] Comparative Example 6:
[0087] The difference from Example 1 is that the viscosity of the low-viscosity silicone gel layer is 200 mPa·s, while all other aspects are the same.
[0088] Test Example 1:
[0089] Objective: To verify the enhancing effect of introducing graphene quantum dots into the film on its electrostatic charge retention ability and to demonstrate its contribution to the electrostatic properties of electrets.
[0090] Experimental sample:
[0091] Sample A (Example 1): Electret therapeutic membrane containing graphene quantum dots.
[0092] Sample B (Comparative Example 1): Therapeutic membrane without graphene quantum dots.
[0093] Experimental equipment and conditions:
[0094] Surface potential tester (non-contact electrostatic voltmeter);
[0095] Constant temperature environment chamber (25℃±2℃, relative humidity 50%±5%);
[0096] Grounding metal platform;
[0097] Initial charge injection device (standard electrostatic generator, fixed injection potential).
[0098] The experimental steps are as follows:
[0099] 1. Sample preparation:
[0100] Sample A and Sample B were cut into square films of the same area (5cm×5cm).
[0101] Place the two sets of diaphragms on a grounded metal platform.
[0102] 2. Charge injection:
[0103] A fixed voltage (+3000V) was applied to the sample surface using an electrostatic generator for 30 seconds to ensure that a stable initial electrostatic state was formed on the surface.
[0104] Immediately after injection, the sample was transferred to a constant temperature chamber for electrostatic decay testing.
[0105] 3. Static electricity monitoring:
[0106] The potential value at the center point of the membrane surface was measured at specific time points (0h, 1h, 3h, 6h, 12h, 24h, 48h, 72h) using a non-contact voltmeter.
[0107] Three readings were collected at each time point, and the average value was taken.
[0108] 4. Data Recording and Processing:
[0109] The potential data were compiled into a table to analyze the decay trend of sample charge over time.
[0110] Calculate the potential retention rate over 72 hours (retained potential / initial potential × 100%).
[0111] The test results are shown in Table 1:
[0112] Table 1. Comparison of Static Electricity Retention Performance (Sample Surface Potential Unit: V)
[0113] Time point (h) Sample A (Example 1) Sample B (Comparative Example 1) 0 3015 2980 1 2820 2435 3 2640 1805 6 2470 1250 12 2305 770 24 2085 430 48 1780 195 72 1505 75
[0114] In the electrostatic retention performance test, the experimental results showed that graphene quantum dots significantly improved the electrostatic charge retention capability of the membrane. According to the experimental data, sample A (the membrane containing graphene quantum dots) exhibited superior charge stability, retaining approximately 50% of its potential after 72 hours. In contrast, comparative sample 1 (the membrane without graphene quantum dots) showed rapid charge decay, with a significant drop in potential within 24 hours, indicating a lack of sustained electrostatic therapeutic function.
[0115] This phenomenon is closely related to the role of graphene quantum dots in composite materials. Graphene quantum dots optimize charge migration paths within the membrane, enhancing its internal conductivity and charge storage capacity. The introduction of graphene quantum dots not only improves the uniformity of charge distribution but also enhances the electrostatic stability of the membrane through its unique electronic structure, allowing it to maintain a high potential over extended periods. This is directly related to the electrostatic therapeutic effect of the membrane; therefore, incorporating graphene quantum dots is crucial for achieving prolonged electrostatic effects.
[0116] In practical applications of electrostatic membrane therapy, charge retention capability is a crucial indicator of therapeutic efficacy. This experiment demonstrates that the introduction of graphene quantum dots enables the membrane to maintain an effective electrostatic field for a longer period, thus ensuring the durability and stability of the therapeutic effect. Membranes without graphene quantum dots lose their electrostatic therapeutic effect within a short time, failing to achieve the therapeutic stability required by this invention. This result further validates the necessity of the innovative composite material design and electrostatic performance optimization in this invention, highlighting the unique role of graphene quantum dots as a key component.
[0117] Test Example 2:
[0118] Objective: To evaluate the effect of the content of nano-cerium oxide particles in composite membranes on their thickness uniformity and mechanical compliance, and to verify the importance of appropriate content for forming structurally stable membranes.
[0119] Experimental sample:
[0120] Sample C (Example 1): A composite membrane with a cerium oxide nanoparticle content of 3 wt%.
[0121] Sample D (Comparative Example 2): A composite membrane with a cerium oxide nanoparticle content of 6 wt%.
[0122] Experimental equipment and conditions:
[0123] Digital micrometer thickness gauge (accuracy ±1μm);
[0124] Flexible testing platform (with standard bending angle module);
[0125] High-speed camera system (used to record deformation and recovery processes);
[0126] Constant temperature room (temperature 25℃±1℃).
[0127] The experimental steps are as follows:
[0128] 1. Thickness uniformity test:
[0129] Each sample was cut into a 5cm×5cm film.
[0130] Twenty-five measuring points (1cm apart) were selected in a grid pattern in the central area of the diaphragm, and the local thickness was measured using a micrometer thickness gauge.
[0131] The standard deviation and coefficient of variation of the thickness data are calculated as quantitative indicators of membrane uniformity.
[0132] 2. Compliance Test:
[0133] The membrane sample was fixed on a flexible testing platform and a standard bending angle (45°) was applied.
[0134] After release, the time required for the membrane to recover to its original state was recorded, and the final static recovery angle was measured.
[0135] Each group was tested 5 times, and the average value was taken.
[0136] 3. Data recording and analysis:
[0137] Compare the differences between the two groups of samples in terms of thickness uniformity and flexibility;
[0138] To determine whether excessive cerium oxide content leads to particle aggregation, rough membrane structure, and decreased mechanical properties.
[0139] The test results are shown in Table 2:
[0140] Table 2 Comparison of Membrane Uniformity and Flexibility Test Results
[0141] index Sample C (Example 1) Sample D (Comparative Example 2) Thickness standard deviation (μm) 6.2 14.7 Thickness variation coefficient (%) 2.1 5.9 Static recovery angle (°) 3.8 9.6 Recovery time (seconds) 0.9 2.5
[0142] In the membrane uniformity and flexibility tests, the experimental results showed that the amount of cerium oxide nanoparticles added significantly affected the overall uniformity and mechanical flexibility of the membrane structure. Sample C, with controlled particle addition, exhibited good thickness consistency, with small standard deviation and coefficient of variation, forming a continuous and dense structure with excellent deformation response. In contrast, the cerium oxide content in sample D increased to 6 wt%, resulting in a significantly uneven membrane thickness distribution, reflecting a trend of imbalance in the internal microstructure of the material.
[0143] This difference stems from the sensitivity of nano-cerium oxide in material dispersion behavior. When the content is moderate, the particles can be fully dispersed in the matrix, filling the gaps between fibers, improving the stability of the composite structure, and helping to maintain the flexibility and adhesion of the membrane. However, when its content exceeds the dispersion threshold, the mutual attraction between particles increases, easily forming agglomeration regions during fiber film formation, leading to localized hard lumps or membrane accumulation, thereby weakening the overall flexibility. This non-uniform structure can also cause stress concentration, causing localized warping or poor adhesion of the membrane during use.
[0144] Based on the material design concept of this invention, the functionality of nano-cerium oxide is not only reflected in its antioxidant capacity but also closely related to the mechanical properties of the membrane. Experiments have verified that precise control of its content is a fundamental condition for achieving uniformity and flexibility, directly affecting whether the membrane can stably conform to complex curved surfaces and maintain the continuity of the electrostatic field and the integrity of the therapeutic contact interface. Therefore, optimizing the addition range of this component is an important manifestation of the synergistic effect of the materials in this invention and one of the indispensable core means to improve membrane performance.
[0145] Test Example 3:
[0146] Objective: To evaluate the effect of silicone gel adhesion layer thickness on the adhesion stability and electrical isolation effect of the membrane at the skin interface, and to verify the importance of silicone gel layer of appropriate thickness for membrane conformability and electrostatic isolation performance.
[0147] Experimental sample:
[0148] Sample E (Example 1): A composite film with a silicone gel adhesion layer thickness of 0.1 mm.
[0149] Sample F (Comparative Example 3): A composite film with a silicone gel adhesion layer thickness of 0.05 mm.
[0150] Experimental equipment and conditions:
[0151] Current leakage testing device (constant electric field simulation equipment);
[0152] Skin model (artificial skin simulation material);
[0153] Digital multimeter (for current measurement);
[0154] Tensile tester (for precise measurement of peel force).
[0155] The experimental steps are as follows:
[0156] 1. Sample preparation:
[0157] Sample E and sample F were cut into films of the same size (5cm×5cm) and attached to the skin model.
[0158] Repeat the operation 5 times for each sample group to ensure data reliability.
[0159] 2. Electrical isolation test:
[0160] A voltage (+100V) is applied to the membrane, and the current leakage between the membrane and the skin model is detected by a current measuring instrument.
[0161] The current leakage was measured three times independently on each sample group, and the average value was calculated.
[0162] 3. Adhesion stability test:
[0163] A tensile testing instrument was used to perform a peel force test on the membrane to determine the maximum force required for the membrane to detach from the surface of the skin model.
[0164] Each sample group was tested 5 times, and the maximum peel force was recorded.
[0165] 4. Data recording and analysis:
[0166] Record current leakage and peel force data to analyze the differences in electrical isolation performance and adhesion stability of the membrane.
[0167] The effect of silicone gel layer thickness was verified by comparing the performance of sample E and sample F in terms of current leakage and peel force.
[0168] The test results are shown in Table 3:
[0169] Table 3 Comparison of performance test results for the bonding interface
[0170] index Sample E (Example 1) Sample F (Comparative Example 3) Current leakage (μA) 0.3 1.2 Maximum peel force (N) 0.15 0.07 Standard deviation of current leakage (μA) 0.1 0.3 Standard deviation of peel force (N) 0.03 0.02
[0171] In the adhesion interface performance test, the experimental data clearly reflected the crucial role of the silicone gel layer thickness in maintaining the adhesion stability and electrical isolation performance of the membrane. Sample E, using a silicone gel adhesion layer of appropriate thickness (0.1 mm), exhibited good adhesion and low current leakage when applied to the skin model, effectively ensuring the tight fit and interfacial insulation of the membrane. Sample F, however, due to insufficient adhesion layer thickness (only 0.05 mm), was prone to instability such as edge lifting and detachment during application. Simultaneously, the interfacial current leakage value increased significantly, indicating that it could not sustainably form an insulating state during electrostatic treatment.
[0172] These performance differences are closely related to the buffering and regulation mechanism of the silicone gel layer in the composite membrane structure. A thicker silicone gel layer forms a flexible transition zone at the bonding interface, which not only adapts to the micro-surface undulations of the skin and enhances adhesion, but also mitigates electric field disturbances caused by minute displacements, improving the interfacial electrical stability between the membrane and the skin. Conversely, insufficient thickness can easily lead to stress concentration, reduced adhesion area, increased risk of interfacial conductivity, and severely weaken the membrane's electric field control capability, making it difficult to support its functional requirements in charge therapy scenarios.
[0173] From the perspective of membrane functional design, the silicone gel layer not only serves the function of adhesion and fixation, but also plays a role in interface regulation and electrical insulation. Its thickness control directly affects the application comfort and continuity of electrostatic therapeutic effect of the membrane in practical applications. This experiment verifies the effectiveness of the integrated design of the adhesion layer structure and function, demonstrating the necessity of the synergistic effect of each layer in this invention for optimizing the performance of the electrostatic therapeutic membrane, and further supporting the promotion value of this composite structure in clinical dielectric adhesive materials.
[0174] Test Example 4:
[0175] Objective: To evaluate the impact of charge injection during film fabrication on surface electrostatic field strength and electret properties, thereby verifying the necessity of this step for achieving an effective electret state.
[0176] Experimental sample:
[0177] Sample G (Example 1): Electret membrane treated with charge injection.
[0178] Sample H (Comparative Example 4): Membrane without charge injection treatment.
[0179] Experimental equipment and conditions:
[0180] Surface electrostatic potential meter (resolution ±1V);
[0181] Electric field excitation detection device (used to verify the charge excitation response of the membrane);
[0182] Constant temperature testing platform (temperature 25℃±2℃, humidity 45~55%);
[0183] Standard grounding device.
[0184] The experimental steps are as follows:
[0185] 1. Sample fixation and pretreatment:
[0186] Cut samples G and H to the same size (5cm×5cm) and place them on a standard grounded platform;
[0187] Check that the sample surface is clean to ensure that testing errors are minimized.
[0188] 2. Electrostatic potential test:
[0189] The initial surface potential of the two groups of samples was measured using a surface potentiometer (Note: no additional charging was performed).
[0190] For each sample, measurements were taken at three points (the center of the membrane and both sides), and the average value was recorded.
[0191] 3. Electric field response test:
[0192] Bring the membrane close to the electric field excitation detector and record whether it can elicit an electrostatic response without contact.
[0193] Determine whether the membrane forms an effective electrostatic field.
[0194] 4. Data recording and analysis:
[0195] Compare the differences in surface electrostatic potential and electrostatic response capability between sample G and sample H;
[0196] Analyze whether the loss of electret properties is due to the lack of injected charge.
[0197] The test results are shown in Table 1:
[0198] Table 4 Comparison of Electret Performance Activation Capability
[0199] Test metrics Sample G (Example 1) Sample H (Comparative Example 4) Surface electrostatic potential (V) 1730 58 Electric field response intensity (level 1-5) 5 1 Potential difference between test points (maximum value / V) 82 7
[0200] In the electret performance activation capability test, the experimental data clearly demonstrates the importance of charge injection treatment for the formation of a stable electret state in the film. Sample G, after charge injection treatment, exhibited a surface electrostatic potential exceeding 1700V and displayed a strong electric field response in a non-contact state, indicating that a stable and perceptible electret electric field had formed on its surface. Conversely, sample H, without charge injection treatment, only exhibited a potential value close to the noise floor level, and its electric field response was almost unmeasurable, indicating that it lacked electret characteristics.
[0201] This phenomenon is closely related to the charge trapping and storage mechanism within the material. Charge injection, as the activation process for achieving the electret state, enables the trap sites within the material to fully acquire and lock free charges, thereby establishing a persistent electrostatic field on the membrane surface. Without this step, even if the membrane has an electret structure design, it is difficult to automatically form an effective charge distribution and maintain the required electric field strength during use. This chain-response relationship between structure, process, and performance is an indispensable foundation for realizing electret functionality.
[0202] From the overall design logic of functional membrane materials, the formation of the electret state depends not only on the material's electronic structure and microstructure, but also on specific activation processes to impart performance expression. The charge injection process, as a step in activating material performance, directly determines whether the membrane can enter a highly efficient working state. The experimental results further verify that this activation step plays an irreplaceable role in the entire composite structure design, serving as a core means to ensure the membrane possesses a stable charge field, and also demonstrating the unique optimization strategy of this invention in the electret technology path.
[0203] Test Example 5:
[0204] Objective: To test the changes in surface charge retention capacity of membranes with different thermal stability designs under elevated temperatures, thereby evaluating the enhancing effect of thermally stable components on charge retention performance and verifying the applicability of the membranes in clinical or complex external thermal environments.
[0205] Experimental sample:
[0206] Sample I (Example 1): A composite film with thermally stable additives (such as polyimide modifiers).
[0207] Sample J (Comparative Example 5): Composite membrane without any added thermally stable components.
[0208] Experimental equipment and environmental conditions:
[0209] Temperature-controlled ambient chamber (temperature control range: 25℃–80℃);
[0210] Surface potential meter (resolution ±1V);
[0211] Sample holder (equipped with standard positioning and grounding functions).
[0212] The experimental steps are as follows:
[0213] 1. Sample preparation and heat treatment:
[0214] Cut sample I and sample J into 5cm×5cm pieces and fix them on the support respectively;
[0215] Place it in a constant temperature chamber set at 60℃ to simulate a mild heating or external heat stimulation environment;
[0216] Maintain constant temperature for 6 hours, and keep the humidity constant (relative humidity approximately 50%) during the test.
[0217] 2. Surface potential measurement:
[0218] Remove the sample immediately after heating and allow it to return to room temperature naturally.
[0219] The potential values were measured at three locations on the membrane surface: the center and the edge, using a potential meter, and the average value was recorded.
[0220] Each sample group was tested three times to assess its ability to retain charge after heating.
[0221] 3. Data Analysis:
[0222] The potential of the membrane remained at a level under different heat treatment conditions.
[0223] The analysis aimed to determine whether the addition of thermally stable components alleviated charge dissipation caused by thermal excitation.
[0224] The test results are shown in Table 5:
[0225] Table 5 Comparison of Thermal Stability and Charge Retention Synergistic Test Results
[0226] Test metrics Sample I (Example 1) Sample J (Comparative Example 5) Potential before heating (V) 1630 1595 Potential (V) after heating 1235 530 Percentage of potential decrease (%) 24.2 66.8 Potential fluctuation range between test points (V) 45 110
[0227] In the synergistic test of thermal stability and charge retention, experimental data showed that the charge retention capacity of the film under heated conditions is closely related to whether a thermally stabilizing component is introduced into its material system. Sample I in Example 1, after being continuously heated at 60°C for 6 hours, still maintained a surface potential exceeding 1200V, showing only a slight decrease in potential, demonstrating good charge retention capacity and thermal response stability. In contrast, sample J, without the introduction of a thermally stabilizing component, experienced a sharp drop in potential under the same conditions, indicating significantly insufficient charge retention capacity and a tendency for a substantial decay in surface potential due to thermal excitation.
[0228] This performance difference stems from the structural mechanism of thermally stable materials at the molecular scale. The introduction of thermally stable components, such as polyimide-modified materials, imparts a higher glass transition temperature and greater molecular chain thermal inertia to the membrane, reducing chain segment movement caused by thermal disturbances and effectively locking charges within the internal trap structure. These materials also provide a denser electrical insulation network, reducing charge migration channels under thermal activation. Conversely, membranes without thermal stabilization exhibit increased chain segment mobility and accelerated charge escape rates under thermal stress, making it impossible to maintain an effective electret state and affecting the membrane's reliability in subsequent functional applications.
[0229] Based on the composite membrane material design concept of this invention, the rational introduction of thermally stable components not only improves the physical structural stability of the membrane under thermal environments but also significantly enhances the durability of its electrostatic field performance. This experiment verifies the synergistic mechanism between the material's functional structure, namely, optimizing charge retention capability through thermal stability regulation, which is one of the key pathways for achieving high-performance electret membrane materials in this invention. This strategy provides reliable electric field protection for the membrane under high-temperature or surface application environments, effectively broadening its application adaptability and clinical applicability.
[0230] Test Example 6:
[0231] Objective: To test the adhesion and electrostatic properties of composite membranes after repeated application and peeling, thereby evaluating the role of structural design in ensuring the performance stability of membranes under repeated use.
[0232] Experimental sample:
[0233] Sample K (Example 1): A composite membrane with a flexible support layer and a slow-release structure design.
[0234] Sample L (Comparative Example 6): The control membrane without a flexible support structure.
[0235] Experimental equipment and conditions:
[0236] Multi-station cyclic bonding and peeling test device (controlling bonding speed and angle);
[0237] Artificial skin model (simulating the object to be attached);
[0238] Surface potential measuring instrument;
[0239] Environmental control box (temperature 25℃±2℃, humidity 45~55%).
[0240] The experimental steps are as follows:
[0241] 1. Cyclic attachment-peeling process:
[0242] Sample K and sample L were respectively attached to the artificial skin model;
[0243] The mechanical device is used for automated attachment and peeling, maintaining the adhesion for 5 minutes each time, and then peeling at a 90° angle.
[0244] Each sample group underwent 50 complete attachment-removal cycles.
[0245] 2. Adhesion performance evaluation:
[0246] After every 10 cycles, the maximum peel force of the membrane was measured using a tensile tester, and its change with the number of cycles was recorded.
[0247] Assess whether the adhesion performance decreases with the number of uses.
[0248] 3. Surface electrostatic properties test:
[0249] After the 0th, 25th and 50th cycles, the surface potential of the samples was measured.
[0250] At each time point, three locations (center and both sides) were measured, and the average potential value was recorded.
[0251] 4. Data Analysis:
[0252] Compare the trends of adhesion strength and charge retention capability of the two groups of samples after multiple uses;
[0253] Analyze the impact of composite structure design on performance retention.
[0254] The test results are shown in Table 6:
[0255] Table 6 Comparison of Performance Retention Test Results After Multi-Cycle Adhesion-Peeling
[0256]
[0257] In multi-cycle adhesion-peel performance retention tests, experimental results showed that the membrane's ability to maintain adhesion and electrostatic properties after repeated use is closely related to the flexible support and slow-release mechanism in its structural design. In Example 1, sample K maintained high peel force and surface potential after 50 adhesion-peel cycles, demonstrating significant performance durability. In contrast, Comparative Example 6 sample L experienced rapid performance degradation under the same conditions, exhibiting insufficient peel force and a sharp decrease in potential value, indicating that its structure lacked the buffering and adjustment capabilities to cope with repeated mechanical actions, making it difficult to achieve functional continuity.
[0258] This performance difference is attributed to the synergistic effect of the flexible support layer and the interface adhesion design in the composite structure. During multiple attachment processes, the membrane must withstand repeated stretching, shearing, and deformation. Without an elastic rebound structure and stress dispersion mechanism, the interface is prone to fatigue damage and uneven peeling, thus accelerating the failure of the adhesion layer. Simultaneously, the electrostatic functional layer is also susceptible to localized charge migration and dissipation under repeated mechanical disturbances. Sample K maintains overall deformation coordination through the flexible support layer and gradually releases adhesion stress through a slow-release structure, effectively delaying fatigue accumulation and stabilizing charge distribution, thereby ensuring performance over multiple cycles.
[0259] From the perspective of overall material design, the composite membrane structure in this invention emphasizes structural-functional synergy. By introducing a multi-layer configuration with elastic recovery and charge retention capabilities, the membrane can maintain stable interfacial adhesion and potential levels even after repeated physical disturbances. The experimental results further verify the adaptability of this multi-layer composite strategy in reusable scenarios, providing stable support for membrane applications such as reusable application and maintenance of dielectric therapeutic effects. It also demonstrates the unique advantages of this invention in the long-term service performance of adhesive electret functional membranes.
[0260] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An electret electrostatic therapeutic membrane, characterized in that, By weight percentage, the therapeutic membrane comprises a composite nanofiber material with the following components: Fluorinated polyether ester 15-20%; 1-2% carboxymethyl chitosan; The nano-cerium oxide particles comprise 2-5% of the total content, with a particle size of 50-100 nm. Graphene quantum dots have a particle size of 0.5-1.0% and a particle size of 5-10 nm; Sodium hyaluronate 1-2%; The components are formed into nanofiber membranes by electrospinning and then subjected to charge injection treatment to obtain electret properties. The composite nanofiber membrane is attached to a flexible adhesive layer and covered with a release film.
2. The electret electrostatic therapy membrane according to claim 1, characterized in that, The flexible adhesive layer is a low-viscosity silicone gel layer with a viscosity of 100–150 mPa·s and a coating thickness of 0.1–0.3 mm.
3. The electret electrostatic therapy membrane according to claim 1, characterized in that, The fluorinated polyether ester is dissolved in a mixed solvent consisting of tetrahydrofuran and dimethylformamide in a volume ratio of 1:1 to 1.
2.
4. The electret electrostatic therapy membrane according to claim 1, characterized in that, The electret performance is achieved by a pulsed plasma charge injection process, with an injection voltage of 15–20 kV and a corona treatment time of 8–12 minutes.
5. A process for preparing an electret electrostatic therapeutic film as described in any one of claims 1-4, characterized in that, Includes the following steps: 1) Preparation of fluorinated polyether ester solution: Dissolve fluorinated polyether ester in a mixed solvent composed of tetrahydrofuran and dimethylformamide, and stir at 25-30℃ for 2-3 hours to form a uniform and transparent solution; 2) Prepare carboxymethyl chitosan solution and sodium hyaluronate solution respectively, with a concentration of 1-2%, and stir at 25-30℃ for 1-2 hours to obtain a uniform hydrosol; 3) Preparation of nano-cerium oxide dispersion and graphene quantum dot dispersion: Nano-cerium oxide particles and graphene quantum dots were added to a mixed solvent of tetrahydrofuran and dimethylformamide, and dispersed by ultrasonic treatment at a power of 100-200W and a time of 30-60min to obtain a uniform dispersion. 4) Add the nano-cerium oxide dispersion, graphene quantum dot dispersion, carboxymethyl chitosan solution and sodium hyaluronate solution to the fluorinated polyether ester solution in sequence, and stir for 30-60 minutes to obtain the composite spinning solution; 5) Nanofiber membranes were prepared by electrospinning, wherein the spinning voltage was 20-25 kV, the spinning solution spraying rate was 0.6-1.0 mL / h, the distance between the spraying end and the receiving end was 10-12 cm, and the spinning time was 2-3 h. 6) The nanofiber membrane is subjected to pulsed plasma charge injection treatment, with the treatment frequency set to 5kHz, the discharge voltage to 15-20kV, the treatment time to 8-12min, the pulse time to 5-7s, the interval time to 2-3s, and the treatment environment to air with a relative humidity of 30-35%. 7) The treated membrane was left to stand at room temperature for 12–14 hours to stabilize the surface charge; 8) The membrane is bonded and assembled with a pre-prepared flexible silicone gel adhesive layer, which is a low-viscosity silicone gel layer with a thickness of 0.1-0.3 mm and a viscosity of 100-150 mPa·s uniformly coated on the surface of the polyethylene terephthalate membrane and dried at 40-45°C for 1-2 hours. After bonding, a release film is applied to obtain the final product.
6. The preparation process according to claim 5, characterized in that, The ultrasonic dispersion of the prepared nano-cerium oxide dispersion and graphene quantum dot dispersion uses the same tetrahydrofuran and dimethylformamide mixed solvent as in step 1), the dispersion temperature is room temperature, and the dispersion time is 30-60 min.
7. The preparation process according to claim 5, characterized in that, The electrospinning process is carried out in an environment with a relative humidity of 30-40% and a temperature of 22-25℃.
8. The preparation process according to claim 5, characterized in that, The low-viscosity silicone gel layer is obtained by uniformly coating a silicone gel with a thickness of 0.1 to 0.3 mm on the surface of a PET film and drying it at 40 to 45°C for 1 to 2 hours.
9. The preparation process according to claim 5, characterized in that, The order of addition of the components in the spinning solution is as follows: nano-cerium oxide particles, graphene quantum dots, carboxymethyl chitosan, and sodium hyaluronate.
10. The preparation process according to claim 5, characterized in that, The final product is vacuum-sealed and stored at 15–25°C, relative humidity 30–40%, and in a light-protected environment.
Citation Information
Cited By
Composite electret flexible biological electrostatic electret patch and preparation method thereof
CN121971609A
A composite electret flexible bioelectrostatic electret patch and its preparation method
CN121971609B